Persepsi Masyarakat Mengenai Tantangan Penegakan Hukum terhadap Pelanggaran Penggunaan Bom Ikan di Wilayah Perairan Kota Bontang - Fatmy Yaumil Akhir Jafar; Fitri Noerhidayanti; Fitriyana Fitriyana; Said Abdusysysyahid (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
The practice of fishing using bombs (blast fishing) presents a serious threat to marine ecosystems and the sustainability of coastal communities' livelihoods. Law enforcement against these violations faces complex challenges, especially in large areas of water with limited fleet and patrol personnel. Perpetrators who move quickly and change locations, coupled with the lack of reports from the public due to fear or social ties, further complicate enforcement efforts. In addition, access to hidden locations and coordination between law enforcement agencies that are not optimal are also the main obstacles. Global studies confirm that the lack of effective law enforcement and adequate governance is a significant driver of these destructive practices, even beyond socio-economic factors. Therefore, a comprehensive strategy is needed that includes strengthening integrated marine patrols on a regular basis, imposing strict sanctions, increasing socialization of the dangers of fish bombs, and the active involvement of coastal communities as supervisors. A synergistic approach between law enforcement officials and local communities, combining prevention and joint management measures, is key to achieving effective marine conservation and sustainable management of fishery resources.